DESIGN OF INTERACTIVE LEARNING MULTIMEDIA MATERIALS OF BATIK JUMPUT ON SBdP SUBJECTS IN ELEMENTARY SCHOOL - Ardian Arief; Dwi Susanti (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Designing Interactive Multimedia Learning for Batik Jumput for SBdP Subjects at SD Negeri Gambiran seeks to produce interactive multimedia learning at SD Negeri Gambiran and establish the feasibility of the development's outcomes based on expert opinion and student comments. This research is design and development research. The subjects of this study are students of class V of Gambiran State Elementary School. This development model refers to the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. Method of data collection with observations, interviews and questionnaires. Eligibility assessments involve experts and learners' responses. The results of this study are; (1) Interactive Multimedia batik jumput SBdP subjects; (2) Interactive multimedia is worth using both in terms of material and visual appearance. The feasibility of interactive multimedia is based on assessments from media experts, material experts, teachers with 87.5%, 92.5%, 97.5%, respectively